Bloodstream infections epidemiology and clinical outcomes after 1 year post allogeneic hematogenous stem cell transplantation - Corcione, Silvia; Longo, Bianca Maria; Rugge, Walter; De Benedetto, Ilaria; Lupia, Tommaso; Shbaklo, Nour; Zompi, Sofia; Gill, Jessica; Curtoni, Antonio; Passera, Roberto; Busca, Alessandro; Bruno, Benedetto; et al. (Frontiers in Microbiology, 2025)
BackgroundBloodstream infections (BSIs) are a serious threat for patients undergoing allogenic hematopoietic stem cell transplants (a-HSCT). MDR colonization is highly prevalent among a-HSCT patients, due to drug-induced intestinal dysbiosis. Primary outcome of the study was to assess the epidemiology and risk factors for BSIs in the 1st year after a-HSCT. Secondary endpoints were to examine the prevalence of MDR bacterial colonization and factors affecting 1-year post-transplant overall survival (OS).MethodsIn this single-center observational cohort study, all consecutive adult patients undergoing a-HSCT for hematological malignancies between 2012 and 2021 were retrospectively enrolled at the Stem Cell Transplant Center, AOU Città della Salute e della Scienza, Turin (Italy). Cumulative Incidence and risk factors for BSIs were analyzed by Gray and Fine-Gray tests, respectively. OS was evaluated with Kaplan–Meier, while the influence of covariates on OS with Cox regression analysis.ResultsTwo hundred and seventy nine patients were enrolled in the study, 43% of which developed BSI within the 1st-year post-transplant. The median onset of BSIs was 10 days after a-HSCT and Gram-negative bacteria were the most common causative agents (58.3%). 20.8% of patients had a positive rectal swab (RS) for MDR bacteria, with extended-spectrum β-lactamases (ESBLs)-producing Enterobacterales being the most common colonizers (60.3% of positive RS), followed by carbapenem-resistant Enterobacteriaceae (CRE) (29.3%). Multivariate competing risks regression analysis showed that colonization by MDR bacteria was associated with a higher incidence of BSIs (SDHR 1.49, 95%CI 1.01–2.20), along with the type of underlying disease (SDHR 0.73, 95%CI 0.58–0.91), donor type (SDHR 1.62, 95%CI 1.02–2.58) and an advanced disease status at the time of transplantation (SDHR 1.57, 95%CI 1.05–2.35). One-year mortality rate was 25.4%. RS colonization was not associated with increased mortality; while BSIs adversely affected OS (SDHR 1.52, 95%CI 1.02–2.26).ConclusionsBSIs are common complications in a-HSCT, with evidence suggesting a negative impact on OS. Although MDR colonization is not independently linked to increased mortality in a-HSCT, it appears to be associated with an elevated risk of subsequent BSI development. These findings underscore the potential value of pre-transplant surveillance, contact precautions, and early targeted antimicrobial therapy in colonized patients to help mitigate infection-related morbidity and mortality.